SWEET17, a Facilitative Transporter, Mediates Fructose Transport across the Tonoplast of Arabidopsis Roots and Leaves - Guo, Woei-Jiun; Nagy, Reka; Chen, Hsin-Yi; Pfrunder, Stefanie; Yu, Ya-Chi; Santelia, Diana; Frommer, Wolf B.; Martinoia, Enrico (Plant physiology (Bethesda), 2014)
Fructose (Fru) is a major storage form of sugars found in vacuoles, yet the molecular regulation of vacuolar Fru transport is poorly studied. Although SWEET17 (for SUGARS WILL EVENTUALLY BE EXPORTED TRANSPORTERS17) has been characterized as a vacuolar Fru exporter in leaves, its expression in leaves is low. Here, RNA analysis and SWEETY7-β-glucuronidase/-GREEN FLUORESCENT PROTEIN fusions expressed in Arabidopsis (Arabidopsis thaliana) reveal that SWEET17 is highly expressed in the cortex of roots and localizes to the tonoplast of root cells. Expression of SWEET17 in roots was inducible by Fru and darkness, treatments that activate accumulation and release of vacuolar Fru, respectively. Mutation and ectopic expression of SWEET17 led to increased and decreased root growth in the presence of Fru, respectively. Overexpression of SWEET17 specifically reduced the Fru content in leaves by 80% during cold stress. These results intimate that SWEET17 functions as a Fru-specific uniporter on the root tonoplast. Vacuoles overexpressing SWEET17 showed increased [¹⁴C] Fru uptake compared with the wild type. SWEET17-mediated Fru uptake was insensitive to ATP or treatment with NH₄Cl or carbonyl cyanide m-chlorophenyl hydrazone, indicating that SWEET17 functions as an energy-independent facilitative carrier. The Arabidopsis genome contains a close paralog of SWEET17 in clade IV, SWEET16. The predominant expression of SWEET16 in root vacuoles and reduced root growth of mutants under Fru excess indicate that SWEET16 also functions as a vacuolar transporter in roots. We propose that in addition to a role in leaves, SWEET17 plays a key role in facilitating bidirectional Fru transport across the tonoplast of roots in response to metabolic demand to maintain cytosolic Fru homeostasis.